Some aspects of chest trauma: Diaphragm breaks - Martínez, José Luis; Salisbury, Siul; Chifflet, Juan (Cirugía del Uruguay, 1997)
Its earliest description was done in 1578 by Paré while the earliest repair was carried out by Walker in the 19th century Diaphragm